2014
DOI: 10.1186/1471-2369-15-104
|View full text |Cite
|
Sign up to set email alerts
|

Avoidance of systemic anticoagulation during intermittent haemodialysis with heparin-grafted polyacrilonitrile membrane and citrate-enriched dialysate: a retrospective cohort study

Abstract: BackgroundSince October 2010, the combination of a heparin-grafted polyacrilonitrile (AN69ST) membrane with a 0.80 mmol/L citric acid-containing dialysate is routinely used in our centre for intermittent haemodialysis, without systemic anticoagulation, in critically ill patients with increased bleeding risk. The primary outcome of this retrospective cohort study was to assess the development of circuit clotting during these dialysis procedures. Secondly, we assessed the impact of clotting on treatment duration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 22 publications
2
22
1
Order By: Relevance
“…These authors recorded a similar incidence of early HD termination due to severe clotting but did not report any details on overall circuit loss [12]. The circuit loss seen in our study is comparable to that in published adult studies using citrate-based dialysate [13]. It is possible that we noted a higher thrombosis rate as we charted any circuit clot and not just dialyzer clotting.…”
Section: Discussionsupporting
confidence: 87%
“…These authors recorded a similar incidence of early HD termination due to severe clotting but did not report any details on overall circuit loss [12]. The circuit loss seen in our study is comparable to that in published adult studies using citrate-based dialysate [13]. It is possible that we noted a higher thrombosis rate as we charted any circuit clot and not just dialyzer clotting.…”
Section: Discussionsupporting
confidence: 87%
“…Only a few studies comparing acetate to CD have been performed. Francois et al [8] reported the avoidance of systemic heparin during intermittent HD while combining a heparin-grafted AN 69 dialyzer with CD in 81% of sessions. One large prospective study in 277 HD patients by Sands et al [9] demonstrated that CD can reduce heparin dosage by 33%.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, our study described the outcomes of HD sessions using only an AN69ST membrane or only a citrate- enriched dialysate. We found that few sessions needed to be terminated prematurely: that is, 8.7% of patients treated with citrate-enriched dialysate compared to 12.7% of patients treated with AN69ST membrane, when compared to that reported by François et al [16]. …”
Section: Discussionmentioning
confidence: 82%